Development of a questionnaire on teachers' knowledge of language as an epistemic tool. Issue 4 (17th September 2020) - Fulmer, Gavin W.; Hwang, Jihyun; Ding, Chenchen; Hand, Brian; Suh, Jee K.; Hansen, William
Abstract: We report on the development of a new instrument for measuring teachers' knowledge of language as an epistemic tool in science classes. Language is essential for science learning, as all learning requires the use of language to constitute one's own ideas and to engage with others' ideas. Teachers with knowledge of language as an epistemic tool can recognize the ways that language allows students to generate and validate knowledge for themselves, rather than to replicate canonical knowledge transmitted by other sources. We used a construct‐driven development approach with iterations of domain analysis, item revision, teacher feedback, expert review, and item piloting to address the content, substance, and structure aspects of validity. Data from 158 preservice and in‐service teachers on 27 preliminary items were collected. Findings from Rasch measurement modeling indicate a single dimension fits the items well and can distinguish teachers of higher and lower knowledge. We revised and selected 15 items for an updated instrument. This contributes to ongoing measurement projects and provides a potential instrument for future, broader use by the field to gauge teachers' knowledge of language as an epistemic tool.